2018
DOI: 10.1097/md.0000000000012069
|View full text |Cite
|
Sign up to set email alerts
|

Home-based telehealth exercise training program in Chinese patients with heart failure

Abstract: The results reveal that telehealth exercise training is an effective alternative method for cardiac rehabilitation, especially under the conditions in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
189
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(201 citation statements)
references
References 20 publications
6
189
0
6
Order By: Relevance
“…Of the 9 studies reporting blood pressure as an outcome of digital interventions versus conventional CR, 3 studies showed noninferiority [ 18 , 29 , 41 ], 4 found no significant impact on blood pressure [ 19 , 28 , 31 , 39 ], and 2 reported a better control of blood pressure in the control group as compared to the digital intervention group [ 25 , 35 ]. Similarly, although the majority of studies assessing mood as an outcome reported that digital interventions were noninferior to conventional CR in improving mood [ 22 , 25 , 29 , 30 , 33 ], 4 studies reported no significant improvement in anxiety or depression [ 19 , 24 , 25 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 9 studies reporting blood pressure as an outcome of digital interventions versus conventional CR, 3 studies showed noninferiority [ 18 , 29 , 41 ], 4 found no significant impact on blood pressure [ 19 , 28 , 31 , 39 ], and 2 reported a better control of blood pressure in the control group as compared to the digital intervention group [ 25 , 35 ]. Similarly, although the majority of studies assessing mood as an outcome reported that digital interventions were noninferior to conventional CR in improving mood [ 22 , 25 , 29 , 30 , 33 ], 4 studies reported no significant improvement in anxiety or depression [ 19 , 24 , 25 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 5 studies reported a positive effect on mood in the intervention group [ 22 , 25 , 29 , 30 , 33 ]. A total of 4 studies found that digital interventions had no significant impact on mood [ 19 , 24 , 25 , 42 ]. In total, 2 studies found no significant change in the psychological status between digital intervention and usual care groups [ 35 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CPET, a gold standard with convenient and safe operation, was adopted for assessing patients’ exercise tolerance and developing exercise prescriptions [ 11 ]. With an intervention period of 6 months, which was much longer than the intervention period of other telemonitored intervention studies nationwide [ 27 , 28 ], this study can provide reference for telemonitored cardiac rehabilitation practice in China.…”
Section: Discussionmentioning
confidence: 99%
“…Âèêîðèñòàííÿ òåëåìîí³òîðèíãó òà òåëåðåàá³-ë³òàö³¿ º â³äíîñíî íîâèì, àëå äóaeå ïåðñïåêòèâíèì íàïðÿìîì â êàðä³îðåàá³ë³òàö³¿. Ïîð³âíÿíî ç ì³aeäèñöèïë³íàðíèìè ïðîãðàìàìè âòðó÷àííÿ, ðåà-ë³çàö³¿ ÿêèõ ÷àñòî ïåðåøêîäaeàþòü åêîíîì³÷í³, ãåîãðàô³÷í³ òà áþðîêðàòè÷í³ áàð'ºðè, íå³íâàçèâíèé äèñòàíö³éíèé ìîí³òîðèíã ìîaeå áóòè ð³øåííÿì äëÿ ïðîäîâaeåííÿ ðåàá³ë³òàö³éíî¿ ïðîãðàìè â äîìàøí³õ óìîâàõ òà ñïðèÿííÿ äîãëÿäó çà ïàö³ºíòàìè ïðîòÿãîì òðèâàëîãî ÷àñó [7,8,14].…”
unclassified